2010
DOI: 10.1029/2009ja014286
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thundercloud screening charges: Implications for blue and gigantic jets

Abstract: [1] A two-dimensional axisymmetric model of charge relaxation in the conducting atmosphere is used in conjunction with a probabilistic lightning model to demonstrate how realistic cloud electrodynamics lead to the development of blue and gigantic jets. The model accounts for time-dependent conduction currents and screening charges formed under the influence of the thundercloud charge sources. Particular attention is given to numerical modeling of the screening charges near the cloud boundaries. The modeling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(137 citation statements)
references
References 46 publications
(122 reference statements)
12
124
0
1
Order By: Relevance
“…Under these circumstances, it is possible that upper level shear may also play a role by enhancing the mixing at storm top or by differentially advecting the upper charge region downstream of the main central charge [van der Velde et al, 2010]. However, it is thought that the latter would tend to promote IC flashes within the anvil region rather than produce a jet or GJ [Riousset et al, 2010]. Soula et al [2011] proposed that dilution of the upper charge relative to the central charge may also occur when the positively charged anvil is rapidly expanding (horizontally) relative to the central (negative) charge region.…”
Section: 1002/2015jd023383mentioning
confidence: 97%
See 1 more Smart Citation
“…Under these circumstances, it is possible that upper level shear may also play a role by enhancing the mixing at storm top or by differentially advecting the upper charge region downstream of the main central charge [van der Velde et al, 2010]. However, it is thought that the latter would tend to promote IC flashes within the anvil region rather than produce a jet or GJ [Riousset et al, 2010]. Soula et al [2011] proposed that dilution of the upper charge relative to the central charge may also occur when the positively charged anvil is rapidly expanding (horizontally) relative to the central (negative) charge region.…”
Section: 1002/2015jd023383mentioning
confidence: 97%
“…Recent modeling studies indicate that, in terms of an initiation mechanism, enhanced storm top mixing (or lack thereof) may be a key factor in determining whether the upward discharge is a GJ or a jet [Krehbiel et al, 2008;Riousset et al, 2010]. Suzuki et al [2012] showed many blue jets and starters from a very high flash rate storm.…”
Section: 1002/2015jd023383mentioning
confidence: 99%
“…As Riousset et al [2007] show, the modeled discharges share many similarities with real discharges. Recently, bidirectional leader models have been used by Krehbiel et al [2008] and Riousset et al [2010] to explain how lightning discharges can grow out of the cloud and strike Earth, or instead escape out of the cloud top as a blue jet or gigantic jet. This occurs when the charge region at the escaping end is weak (shallow potential well) compared to the main charge center.…”
Section: Introductionmentioning
confidence: 99%
“…Recent models [Mansell et al, 2002;Riousset et al, 2007Riousset et al, , 2010 extend branched lightning channels stochastically to a new grid point in its vicinity when the potential difference between lightning channel and surrounding grid points with cloud charge exceeds a threshold. The potential on the channel and surroundings is then recalculated and the procedure is repeated until no more new nodes can be found that surpass the threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a certain charge imbalance may persist in thunderstorm, which causes strong variations of the electric field with altitude. Recently, Krehbiel et al (2008) and Riousset et al (2010b) have discussed a stratiform/multilayered thundercloud model to demonstrate the difference between the conditions for downward-propagating discharges in the form of usual −CG lightning and for upward-propagating discharges like jets. The charged regions situated at different altitudes in the thundercloud are sketched in Fig.…”
Section: Effect Of Charge Distribution In Thunderclouds On Jet Dischamentioning
confidence: 99%